Exploring the nexus between place of residence, daily activity patterns, and the socio‐spatial isolation of mothers on parental leave. Issue 2 (27th October 2019) - Frantál, Bohumil; Klapka, Pavel
Abstract : This paper examines issues concerning mothering and childcare, with an emphasis on two crucial aspects which are based on the fact that mothers' individual behaviours are undoubtedly time‐space dependent. First, unlike the majority of studies which have investigated mothers' isolation by applying qualitative methods, this exploratory study using data from the Czech Republic is based on a time‐geographical approach using time‐space diaries, a questionnaire survey, and statistical analyses of quantitative data. Second, the paper examines the interrelationship between real time‐space activity patterns and perceived senses of loneliness and isolation. The model of socio‐spatial isolation developed here suggests that such isolation is significantly affected by the place of residence, work activity, household income, and frequency of performing leisure activities, particularly making trips into the countryside, attending cultural events, meeting friends, and taking time for self‐care. Mothers' clubs, which are significantly more often visited by urban mothers, serve as places for sharing common problems, but they do not reduce perceptions of isolation. Isolation is more likely to be perceived by rural mothers, and mothers from lower income households who do not have any part‐time work during parental leave. One‐third of Czech mothers, however, still hold the traditional view that responsible mothers primarily care for children and do not work during parental leave. The absence of any part‐time work negatively affects not only women's professional and personal lives but also their economic status, which further limits their possibilities for leisure‐time activities and increases their socio‐spatial isolation. In this respect, policy interventions should seek to improve the possibilities of flexible working for mothers as well as to develop programmes and options for leisure‐time activities, particularly for mothers from low‐income families living in rural areas. Abstract : This paper considers issues concerning mothering and childcare, with an emphasis on two crucial aspects based on the fact that mothers' individual behaviours are undoubtedly time‐space dependent. First, unlike the majority of studies which have investigated mothers' isolation by applying qualitative methods, this exploratory study using data from the Czech Republic is based on a time‐geographical approach using time‐space diaries, a questionnaire survey, and statistical analyses of quantitative data. Second, the study examines the interrelationship between real time‐space activity patterns and perceived senses of loneliness and isolation.